Monolithic Structure Technology: A New Construction Process to Enhance Traditional Construction - Belabid, Abderrahim; Akhzouz, Hajar; Elminor, Hannane; Elminor, Hassan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Let’s imagine a low clay soil or aggregates, lime or cement and fibers; how can we create value with these three materials or rather how can we achieve an affordable, sustainable building with low environmental impact that requires less maintenance. The elimination of steel increases the life span of buildings by avoiding the corrosion of steel through the phenomenon of the concrete carbonation. So what is the proposed mix and with what mode can we build. The objective of this paper is to propose and evaluate a new construction technology: the technology of monolithic structures applied to low-rise buildings. This technology focuses on the valorization of local materials through a modern construction process. Thus, in this paper we will describe this process, propose and analyze the adequate models in materials and architecture. Finally we will analyze the feasibility, the ecological and economic profitability of this technology. This construction process uses the same ingredients as traditional buildings, but with innovative approaches in design and execution.